Macroeconomic Conditions, World Capital Market, and Commodity Price on The Jakarta Composite Index - Dasman, Sunita; Purnomo, Grenda Galih; Wulandari, Dian Sulistyorini (Proceeding International Pelita Bangsa, 2023)
The company's activities in the capital market such as the Indonesian Stock Exchange securities can be seen from the Stock Price Index combined. There are many factors that affect the JCI such as macro-economic conditions, and commodity prices. Factors that can affect the Jakarta Composite Index (JCI) needs to be studied to obtain maximum investment returns. The purpose of this study is to examine the impact of macroeconomic conditions such as inflation, interest rates, the rupiah exchange rate, and economic growth; global capital market index; commodity prices to the composite price index (JCI). This study uses multiple linear regression analysis with step-wise method by using software Eviews version 10. The results of the study show that the increase in the economic growth and world oil prices had an impact on JCI increase. Increase in inflation rates and the gold price have an effect on the decline in the JCI. The Dow Jones Index, The Nikkei 225 Index, and exchange rate had very strong positive correlation with economic growth (GDP). The interest rate has strong positive correlation with the inflation rate.